Parental SES buffers the effect of plasma pTau181 on memory among non‐Latinx White, Latinx, and non‐Latinx Black middle‐aged adults. (20th December 2022) - Manly, Jennifer J; Starks, Tiara M.; Simoes, Sabrina; Turney, Indira C; Lao, Patrick J.; Banjoko, Michael B.; Brickman, Adam M.
Abstract: Background: Inclusive ADRD research should consider social and structural forces as potential sources of cognitive reserve and resilience. Characterization of neuropathology is critical for cognitive reserve research, but few cohorts have AD biomarker data in concert with sufficient sample size, population representativeness, and multi‐level, lifecourse measurement of determinants that is necessary to contribute substantial or novel evidence for when and where to intervene. We partnered with participants in a population‐representative intergenerational study in NYC to determine whether parental socioeconomic status (PSES) buffers the association of plasma pTau181 concentrations with memory among middle aged adults, and whether moderation of neuropathology is similar across racialized and ethnic groups. Method: Offspring participants were 1038 adult children (56±11‐years‐old range: 28‐88, 68% women, 12.6±4 years education, 48% Latinx tested in Spanish, 24% Latinx tested in English, 21% non‐Latinx Black, 7% non‐Latinx White) of 694 parents in a longitudinal community‐based study of Northern Manhattan residents age 65+. Blood collected from Offspring determined pTau181 concentration (Quanterix Simoa) and APOE genotype, and memory was tested with the Selective Reminding Test. PSES was measured with years of school collected directly from parents. Regression models examined associations of pTau181 concentration with memory, tested PSES as an effect modifier, and determined whether relationships differed by racial and ethnic group. Result: In an unadjusted model, higher pTau181 concentrations predicted lower delayed recall (β = ‐0.438, 95% CI:‐0.662, ‐0.214, p<0.001), and this was robust to addition of offspring age, sex/gender, years of education, racial and ethnic classification, APOE status, parental age, and PSES into the model (β = ‐0.332, 95% CI:‐0.542, ‐0.122, p<0.001). pTau181 concentrations had a weaker relationship to delayed recall among offspring with higher PSES (β = ‐0.291, 95% CI: ‐0.540, ‐0.043, p<0.022) than among those with lower PSES (β = ‐0.477, 95% CI:‐0.875, ‐0.078, p = 0.019), and this effect modification was similar in all race and ethnicity groups. Conclusion: Evidence from a multiethnic intergenerational study suggests that early life socioeconomic conditions promote cognitive reserve against AD neuropathology. The buffering effect of parental SES was present in all groups, but because racial and ethnic minoritized groups have disproportionate exposure to low SES in childhood, interventions that reduce childhood poverty could narrow ADRD disparities.